ANALISIS KESULITAN BELAJAR MEMBACA PERMULAAN PADA SISWA KELAS II SDN 3 CILANGKAP - Mia Nurul Silmi; Winarti Dwi Febriani; Riga Zahara Nurani (LPPM Universitas Perjuangan Tasikmalaya, 2021)
The problem in this study is the low ability of students in reading at the beginning of class II SDN 3 Cilangkap. With that the aim of this study is to analyze learning difficulties in reading the beginning. The method used in this research is descriptive qualitative. Data collection techniques using test techniques, observation, and interviews. The results of the study obtained data from 4 people, there were 2 students who were not fluent in reading, including difficulty in recognizing letters, arranging syllables into words, and difficulty distinguishing almost the same letter forms. Then 2 more people began to be able to show fluency in reading. This can be seen when they begin to be able to recognize letters, arrange syllables into words, and are able to distinguish letters that are almost the same at the time of spelling. Of these difficulties, there are factors that cause SDN 3 Cilangkap students to experience difficulty in reading at the start, these factors include intellectual, psychological, and family factors. Based on the explanation above, it can be concluded that there are 4 students who have problems in reading the beginning, while the contributing factors are intellectual, psychological, and family factors.